Staged Stem Cell-enriched Tissue (SET) Injections for Soft Tissue Augmentation in Hostile Recipient Areas: A Preliminary Report - Tiryaki, Tunc; Findikli, Necati; Tiryaki, Demir (SPRINGER, 2011)
Autologous fat transplantation is frequently used for a variety of cosmetic treatments and difficult reconstructive indications such as involutional disorders, hemifacial atrophy, sequelae of radiation therapy, or similar problems. However, the limitations of fat transplantation are well known in such difficult cases, particularly the long-term unpredictability of volume maintenance. The ideal method of preparing autologous fat grafts optimizes tissue survival and reduces the variability of outcomes. We propose that enriching traditionally prepared fat grafts with adipose-derived regenerative cells (ADRCs) represents one such method. Using a staged approach, we performed cell-enriched fat transfer by injecting autologous ADRCs into soft tissue that was recently grafted using traditional methods of fat transfer. Over a 3-year period, data were prospectively collected from 29 patients who underwent a single session of stem cell-enriched tissue injections (SET). Cell-enriched grafts ranged in volume from 10 to 390 cc per recipient area and were obtained by manual or automated processes. The mean follow-up period was 10 months. Postoperative atrophy of the injected tissue was minimal and subjectively did not change after 8 weeks. Of note, historically reported rates of atrophy range from 20 to 80%. All patients were satisfied with the primary result with no need for a secondary session except for the cosmetic cases. These preliminary results suggest that SET is safe and may provide superior results compared to traditional fat grafting. By performing the procedure in a staged approach, operating room expenses are minimized, which ultimately decreases the cost of the procedure. Adipose-derived regenerative cells may mitigate early ischemia by increasing angiogenesis, decreasing apoptosis, and modulating the local inflammatory response. This technique may be of particular value to the surgeon when grafting high volumes of fat or when faced with hostile recipient area conditions, including fibrosis and post radiation.
Keywords: Stem cells; Plastic surgery; SET; Hostile recipient area; Lipoinjection; Tissue engineering; Fat transplantation; Adipose-derived stem cells; Surgery